Molecular Characteristics and Prevalence of Rifampin Resistance in Staphylococcus aureus Isolates from Patients with Bacteremia in South Korea - Yong Kyun Kim; Yewon Eom; Eunsil Kim; Euijin Chang; Seongman Bae; Jiwon Jung; Min Jae Kim; Yong Pil Chong; Sung-Han Kim; Sang-Ho Choi; Sang-Oh Lee; Yang Soo Kim (MDPI AG, 2023)
Rifampin resistance (RIF-R) in Staphylococcus aureus (S. aureus) with rpoB mutations as one of its resistance mechanisms has raised concern about clinical treatment and infection prevention strategies. Data on the prevalence and molecular epidemiology of RIF-R S. aureus blood isolates in South Korea are scarce. We used broth microdilution to investigate RIF-R prevalence and analyzed the rpoB gene mutation in 1615 S. aureus blood isolates (772 methicillin-susceptible and 843 methicillin-resistant S. aureus (MRSA)) from patients with bacteremia, between 2008 and 2017. RIF-R prevalence and antimicrobial susceptibility were determined. Multilocus sequence typing was used to characterize the isolate's molecular epidemiology; Staphylococcus protein A (spa), staphylococcal cassette chromosome mec (SCCmec), and rpoB gene mutations were detected by PCR. Among 52 RIF-R MRSA isolates out of 57 RIF-R S. aureus blood isolates (57/1615, 0.4%; 5 methicillin-susceptible and 52 MRSA), ST5 (44/52, 84.6%), SCCmec IIb (40/52, 76.9%), and spa t2460 (27/52, 51.9%) were predominant. rpoB gene mutations with amino acid substitutions showed that A477D (17/48, 35.4%) frequently conferred high-level RIF resistance (MIC > 128 mg/L), followed by H481Y (4/48, 8.3%). RIF-R S. aureus blood isolates in South Korea have unique molecular characteristics and are closely associated with rpoB gene mutations. RIF-R surveillance through S. aureus-blood isolate epidemiology could enable effective therapeutic management.